(untitled) (Global Journal of Human-Social Science, 2022)
The core problematic of the present study is the relationship between the deaf child and the hearing parents The objectives of the study are to describe the social representations of deafness and psychological suffering among parents of deaf children and to establish the link between their suffering and these social representations It is a cross-sectional study conducted from August 15 2011 to January 16 2012 in the ENT department Oto-Rhino Laryngology of the CHU Teaching hospital Sylvanus Olympio and at the school for the deaf EPHATA in Lom A sample of 127 participants was obtained using the all-comers method The data were collected using the semi-structured interview The results show that the psychological suffering of parents of deaf children is presented on three spheres